2013
DOI: 10.1021/es402795x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Mineralogy, and Solid–Liquid Phase Separation Characteristics of Cu and Zn Precipitates Produced with Biogenic Sulfide

Abstract: The morphology, mineralogy, and solid-liquid phase separation of the Cu and Zn precipitates formed with sulfide produced in a sulfate-reducing bioreactor were studied at pH 3, 5, and 7. The precipitates formed at pH 7 display faster settling rates, better dewaterability, and higher concentrations of settleable solids as compared to the precipitates formed at pH 3 and 5. These differences were linked to the agglomeration of the sulfidic precipitates and coprecipitation of the phosphate added to the bioreactor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…27 Cu(I)-S could thus represent an amorphous Cu sulfide phase with a disordered local structure similar to that of Cu(I)methionine. This hypothesis has been well documented in the literature, for instance Villa-Gomez et al 40 suggested that the instantaneous reaction kinetics and low Cu sulfide solubility over the entire pH range makes Cu sulfide precipitation prevail over the formation of another Cu species, while also leading to the formation of amorphous Cu sulfide precipitates. The studies of Shea and Helz 41 and Pattrick et al 42 also demonstrated the precipitation of amorphous Cu sulfide in batch experiments at room temperature and in anaerobic conditions.…”
Section: Zinc Speciation In Rawmentioning
confidence: 74%
“…27 Cu(I)-S could thus represent an amorphous Cu sulfide phase with a disordered local structure similar to that of Cu(I)methionine. This hypothesis has been well documented in the literature, for instance Villa-Gomez et al 40 suggested that the instantaneous reaction kinetics and low Cu sulfide solubility over the entire pH range makes Cu sulfide precipitation prevail over the formation of another Cu species, while also leading to the formation of amorphous Cu sulfide precipitates. The studies of Shea and Helz 41 and Pattrick et al 42 also demonstrated the precipitation of amorphous Cu sulfide in batch experiments at room temperature and in anaerobic conditions.…”
Section: Zinc Speciation In Rawmentioning
confidence: 74%
“…Among the efforts to synthesize metal sulfide nanostructures of specific physicochemical properties, the biological pathways via microbial sulfate-reduction are gaining noticeable traction being less energy-intensive and eco-friendly. To date, a variety of microorganisms including bacteria, algae, yeasts, and fungi have been, or are being, tested for the ability to synthesize metal sulfide nanoparticles (Bai et al, 2006;Mandal et al, 2006;Zhou et al, 2010;da Costa et al, 2012;Duran and Seabra, 2012;Hazra et al, 2012;Edwards et al, 2013;Miradeh et al, 2013;Su et al, 2013;Villa-Gomez et al, 2013;Mala and Rose, 2014;Moon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…). This sludge settling performance was also much better than that in the SRB process . Furthermore, the moisture content was reduced from 99 to 95% due to the formation of ABGS.…”
Section: Resultsmentioning
confidence: 82%
“…In sulfide precipitation, the source of sulfide can be chemicals (such as Na 2 S) . However, Na 2 S precipitation is always limited by its low‐effective sludge solid–liquid separation.…”
Section: Introductionmentioning
confidence: 99%